.5x-3=-1

Simple and best practice solution for .5x-3=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5x-3=-1 equation:


Simplifying
0.5x + -3 = -1

Reorder the terms:
-3 + 0.5x = -1

Solving
-3 + 0.5x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 0.5x = -1 + 3

Combine like terms: -3 + 3 = 0
0 + 0.5x = -1 + 3
0.5x = -1 + 3

Combine like terms: -1 + 3 = 2
0.5x = 2

Divide each side by '0.5'.
x = 4

Simplifying
x = 4

See similar equations:

| 16x^2-46x+15=0 | | x^2-324=2x | | 2(8x-5)=4 | | -18n=-180 | | 16/7x/2/35x | | 3y^2-14y-5=0 | | -6x^4+36x^3+30x^2= | | 2y=-3x | | 9+x/3=-10 | | v+25=77 | | (7/12)+(5/18) | | 6/102= | | x^2+y=5x-8 | | 102/6= | | 3x-11=-17 | | 3b^2-30b=6b-60 | | (a+2)/2=-1 | | 2x-4/6=6x+2/x-6 | | (-16/11)/(4/9) | | x^2+y+8=5x | | (-1/15)+(-14/15) | | 6x+30=25x-20 | | 2x^2-12x+36= | | d*d+18(d+4)=-9 | | s*s-3(s+2)=4 | | 0=-7.5(x^2-4x-320) | | 5r-15/12r2+24r*6r+12/30-10r | | r=-7.5(x^2-4x-320) | | 2x=16y | | 7*(2/3) | | 5-4y+y=-23 | | x/10+30=45 |

Equations solver categories